Overview of underwater friction stir welding - Noor, N.F.M. (Asian Research Publishing Network, 2016)
Friction Stir Welding (FSW) is the one of the advance welding techniques in current years. It is solid state welding and efficiently can overcome the conventional fusion welding technique weaknesses. FSW involve rotational tool and move along the edge of the two workpieces. The frictional heat and plastic deformation process provide firm condition for the solid state welding to occur. Due to the advantages of solid state welding, formerly the FSW was applied to aluminium alloys rather than hard material. The developments of knowledge in tool level up the FSW application to the hard materials such as steel, stainless steel and even Inconel. Other than that, researchers found that the heat input during welding process is the one of the factor in order to enhance the quality of the joint. Therefore, in FSW areas, researches exploring Underwater Friction Stir Welding (UFSW) to control the heat input during the process and produce good quality of the joint in term of microstructure and mechanical properties. In this paper, relevant researches in UFSW will be discussed and until now, it is found that researches in UFSW are still in basic stage and not many researchers deeply explore it yet. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.